Application of transcranial focused ultrasound in neurosurgery - Kosiachuk, S. L.; Storchak, O. H. (Харківський національний автомобільно-дорожній університет, 2022)
Transcranial focused ultrasound is a modern medical technology that allows a noninvasive neurostimulation on the brain. This technique has been developing for about 20 years and a lot of possible applications of the technology are only at the preclinical research stage. The greatest progress has been made in the field of functional neurosurgery when focused ultrasound allows non-invasive therapy to create small destruction areas in the corresponding targets under constant magnetic resonance imaging (MRI) control to have therapeutic neuromodulatory effects upon Parkinson’s disease, essential tremor, pain syndromes, obsessive-compulsive disorders and other diseases. To date, this treatment has been provided for more than 300 patients. The single cases of the ultrasonic thermal destruction of intracranial neoplasms have been published recently. The attempts of ultrasonic third ventriculostomy are made to treat animals.
Keywords: neurosurgery; technology; noninvasive neurostimulation; transcranial focused ultrasound